Investigating the use of Arbuscular Mycorrhizas and Plant Growth Promoting Bacteria to improve the drought tolerance of maize (Zea mays L.) - Moore, Nicolle Maureen (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2016)
Maize (Zea mays L.) is a direct staple food crop in Africa and remains an essential component of global food security, with maize crops accounting for over 60% of the total harvested area of annual food crops. Stress caused by drought and high soil salinity limits crop growth and productivity more than any other single environmental factor, with grain yield reductions up to 76% depending on the severity of the drought and the plant growth stage. Arbuscular mycorrhizal (AM) fungi and Plant Growth Promotion Rhizobacteria (PGPR) have previously been shown to improve tolerance of plants to drought stress through a number of chemical and physiological processes. The aim of this investigation was to determine whether mycorrhizal fungi and rhizobacteria adapted to drought and saline conditions and possessing plant growth promoting (PGP) traits were able to stimulate plant growth responses when applied to Zea mays seeds growing under greenhouse conditions Bacterial isolates selected were tolerant to concentrations of NaCl up to 600 mM and maintained 50% growth at low water potentials (-1.44 MPa). They were positive for Indole Acetic Acid (IAA) production, phosphate solubilisation and secretion of siderophores. Bacterial isolates showing plant growth promoting potential were identified using 16S rDNA gene sequencing as Achromobacter xylosoxidans strains A8 and C54 and Klebsiella oxytoca strain M1. Mixed inoculum was prepared from indigenous communities of mycorrhizas in soils sampled from the Cerebos Salt Pan and the Kalahari Desert. Mycorrhizal diversity was investigated using 454-Pyrosequencing which revealed that the community composition was dominated by species in the Ambispora, Glomus and Paraglomus genera with a rare component represented by species in the Redeckera, Archaeospora and Geosiphon genera. Microscopic examination of plant roots at the end of the trial revealed the presence of diagnostic mycorrhizal structures within the root cells, confirming that colonization was successful. Plant growth response to microbial inoculation was assessed by monitoring changes in plant photosynthetic capacity over the duration of a 7 week pot trial. A significant difference in photosynthetic and biomass data was observed between drought and well-watered groups but no mycorrhizal or bacterial treatment effect was evident within the groups, despite the high levels of colonization by mycorrhizas. These results suggest that the beneficial effects of mycorrhizal colonization may be primarily attributed to improved nutrient and mineral uptake in conditions where nutrients are limiting, resulting in improved growth. The improved growth may then have secondary effects on the plant"Ÿs ability to withstand drought. Having controlled for nutrient deficiency, it was not evident in this study that mycorrhizal fungi were able to stimulate a change in plant physiology and confer drought tolerance under the conditions imposed.
Keywords: Uncatalogued